Hepatitis C virus infection is associated with hepatic and adipose tissue insulin resistance that improves after viral cure - Lim, T; Hazlehurst, J; Oprescu, A; Armstrong, M; Abdullah, S; Davies, N; Flintham, R; Balfe, P; Mutimer, D; McKeating, J; Tomlinson, J (Wiley, 2018)
Background Chronic hepatitis C (CHC) is associated with systemic insulin resistance, yet there are limited data on the tissue‐specific contribution in vivo to this adverse metabolic phenotype, and the effect of HCV cure. Methods We examined tissue‐specific insulin sensitivity in a cohort study involving 13 patients with CHC compared to 12 BMI‐matched healthy control subjects. All subjects underwent a two‐step clamp incorporating the use of stable isotopes to measure carbohydrate and lipid flux (hepatic and global insulin sensitivity) with concomitant subcutaneous adipose tissue microdialysis and biopsy (subcutaneous adipose tissue insulin sensitivity). Investigations were repeated in seven patients with CHC following antiviral therapy with a documented sustained virological response. Results Adipose tissue was more insulin resistant in patients with CHC compared to healthy controls, as evidence by elevated glycerol production rate and impaired insulin‐mediated suppression of both circulating nonesterified fatty acids (NEFA) and adipose interstitial fluid glycerol release during the hyperinsulinaemic euglycaemic clamp. Hepatic and muscle insulin sensitivity were similar between patients with CHC and controls. Following viral eradication, hepatic insulin sensitivity improved as demonstrated by a reduction in endogenous glucose production rate. In addition, circulating NEFA decreased with sustained virological response (SVR) and insulin was more effective at suppressing adipose tissue interstitial glycerol release with a parallel increase in the expression of insulin signalling cascade genes in adipose tissue consistent with enhanced adipose tissue insulin sensitivity. Conclusion Chronic hepatitis C patients have profound subcutaneous adipose tissue insulin resistance in comparison with BMI‐matched controls. For the first time, we have demonstrated that viral eradication improves global, hepatic and adipose tissue insulin sensitivity.